Assessing the Presence of Library and Information Science Outputs on Social Media Platforms Using Altmetrics - Chingath, Vysakh; Hanumanthappa, Rajendra Babu (Journal of Data Science, Informetrics, and Citation Studies)
The present study is carried out to measure the altmetric presence of Library and Information Science outputs on various social media platforms. Furthermore, the study aimed to determine the correlation between citations and altmetric attention scores. Data for the study were extracted from the Altmetric Explorer. The study findings reported that a total of 31867 LIS outputs were indexed and tracked by Explorer and a total of 24869 (78.03%) outputs were mentioned on various social media platforms. Moreover, LIS outputs were present on 17 major social media platforms with the highest mentions recorded from Mendeley, Twitter and blogs. The journal-wise distribution of attention revealed that outputs published in Scientometrics journal attracted more digital reach as compared to other LIS journals. The highest number of Twitter mentions for the outputs were from the United States with 24420 (15.81%) posts from 10143 (16.93%) profiles followed by the United Kingdom with 16131 (10.45%) posts from 6151 (10.27%) profiles. The study result showed a significant weak positive correlation between citations and altmetric score (rho=0.18, p≤0.001). This is the first of its kind study to explore the altmetrics of LIS in-depth especially with regards to the Dimensions.ai database and the findings of the study give insights to the LIS research community on using altmetrics at par with classic metrics for measuring the instantaneous impact of their research.
Keywords: Library and Information Science; Altmetrics; Social media; Social media metrics; Altmetric attention score.